Outbreaks of Avipoxvirus Clade E in Vaccinated Broiler Breeders with Exacerbated Beak Injuries and Sex Differences in Severity - Ruy D. Chacón; Claudete S. Astolfi-Ferreira; Patrícia C. Pereira; Mario S. Assayag; Antony B. Campos-Salazar; David De la Torre; Lilian R. M. de Sá; Sonia R. Yokomizo de Almeida; Rose Elí Grassi Rici; Antonio J. Piantino Ferreira (Viruses, 2022)
Avipoxvirus affects chickens and wild birds, and it is characterized by lesions on the nonfeathered parts of the body (the cutaneous form), or necrotic lesions in the upper respiratory tract (the diphtheritic form). In poultry farming, avian pox is usually controlled by live attenuated vaccines. However, there have been many reports of outbreaks, even in flocks of vaccinated birds. In the present study, different outbreaks of the emerging clade E avipoxvirus were detected in commercial breeder flocks of chickens vaccinated against fowlpox virus in Southeast Brazil. Clinical manifestations of these outbreaks included a marked prevalence of moderate to severe progressive lesions in the beaks of affected birds, especially in roosters with increased mortality (up to 8.48%). Also, a reduced hatchability (up to 20.77% fewer hatching eggs) was observed in these flocks. Analysis of clinical samples through light and transmission electron microscopy revealed the presence of Bollinger bodies and poxvirus particles in epithelial cells and affecting chondrocytes. PCR, sequencing, and phylogenetic analysis of major core protein (P4b) and DNA polymerase (pol) genes identified this virus as clade E avipoxvirus. We also developed qPCR assays for open reading frames (ORFs) 49, 114, and 159 to detect and quantify this emergent virus. These results show the arrival and initial spread of this pathogen in the poultry industry, which was associated with harmful outbreaks and exacerbated clinical manifestations in vaccinated commercial breeder flocks. This study also highlights the relevance of permanent vigilance and the need to improve sanitary and vaccination programs.